Lipoprotein alterations in endocrine disorders - a review of the recent developments in the field - Olejarz, Michal; Szczepanek-Parulska, Ewelina; Ruchala, Marek (Frontiers in Endocrinology, 2024)
Dyslipidemia is one of the most common disorders worldwide, which, if left untreated, results in a multitude of complications. Thus proper diagnostics, which includes identifying of secondary causes of dyslipidemia is crucial. Endocrine disorders are an important cause of secondary dyslipidemia. This paper aims to review the publications on lipoprotein alterations in endocrine disorders from the past two years and provide an overview of the recent discoveries in this dynamically developing and large field. Significant changes in lipoprotein serum concentrations are present in most endocrinological diseases and can be modified with proper treatment. Some lipoproteins have also been proposed as markers in some endocrine diseases, e.g., thyroid carcinoma. From the scope of endocrine disorders, the largest number of studies explored the lipoprotein changes in polycystic ovary syndrome and in women during the menopausal and peri-menopausal period. Even though the association of thyroid disorders with dyslipidemia is already well studied, new research has delivered some exciting findings about lipoprotein alterations in euthyroid patients with either positive antithyroid peroxidase antibodies or reduced sensitivity to thyroid hormones. The problem of the adverse metabolic profile, including dyslipidemia in hypoprolactinemia has been recognized. Moreover, this review describes other significant discoveries encompassing lipoprotein alterations in disorders of the adrenals, thyroid, parathyroid glands, pituitary, and gonads. The up-to-date knowledge of the influence of endocrine disorders and hormonal changes on serum lipoproteins is prudent as it can significantly impact therapeutic decisions.